2012
DOI: 10.3390/nu4060491
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Ramadan Observance upon Athletic Performance

Abstract: Ramadan observance requires a total abstention from food and drink from sunrise to sunset for a period of one month. Such intermittent fasting has only minor effects upon the overall nutrition and physiological responses of the general sedentary population. Larger meals are consumed at night and in the early morning. Body mass usually remains unchanged, the total energy intake remains roughly constant, and there is little alteration in the relative consumption of protein, fats and carbohydrates. However, Ramad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0
11

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 63 publications
2
32
0
11
Order By: Relevance
“…While the small changes in nutritional intake are unlikely to have any major impact on performance, it is possible that the phase shift in food and fluid intake, and change in sleep patterns could affect physical performance (25). Furthermore, it is shown in previous studies that if subjects maintain hydration and training, there seems at most a very small decrease in muscle contractile force during Ramadan (26). Even though bradycardia and hypotension may also occur during prolonged fasting (27), heart rate and blood pressure remain normal during first few days of fasting.…”
Section: Discussionmentioning
confidence: 99%
“…While the small changes in nutritional intake are unlikely to have any major impact on performance, it is possible that the phase shift in food and fluid intake, and change in sleep patterns could affect physical performance (25). Furthermore, it is shown in previous studies that if subjects maintain hydration and training, there seems at most a very small decrease in muscle contractile force during Ramadan (26). Even though bradycardia and hypotension may also occur during prolonged fasting (27), heart rate and blood pressure remain normal during first few days of fasting.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the participants reported using ephedrine, caffeine, clenbuterol, and synthetic thyroid hormones (T3 and T4) during the cutting phase. Considering that during the pre-contest phase there is an abrupt reduction in nutrients and caloric intake [2][3][4]21], the rationale for the use of stimulant-based substances during this phase is thought to be to avoid the reduced performance and increased perception of effort observed during severe caloric restriction [21,25]. However, the cost-benefit of this practice might be addressed critically, since the use of AAS might increase catecholamine release and β-adrenergic receptor expression [12], which might potentiate the harmful effects of stimulants.…”
Section: Discussionmentioning
confidence: 99%
“…Specific articles have also examined the impact of such practices on fluid balance and physical performance [3–6]. However, there are few reports concerning judokas, and none of the published articles have addressed the specific issue of the contestant who is observing Ramadan and who decides to reduce his/her body mass in the period immediately prior to the weigh-in for a competition.…”
Section: Overviewmentioning
confidence: 99%
“…Most investigators have found that these changes in sleep habits and the altered timing of food and fluid ingestion lead to some deterioration in athletic performance [6, 29]. However, the available data are somewhat conflicting.…”
Section: Overviewmentioning
confidence: 99%